Women’s Career Advancement in Nepalese Organization - Shrestha, Beechana (Nepalese Journal of Business, 2025)
This study examines the determinants of glass ceiling and other factors on women’s career advancement in Nepalese organization. Women’s career advancement is selected as the dependent variable. Similarly, glass ceiling, mentoring, networking, organizational structure and family barrier are selected as the independent variables. This study is based on primary data with 121 observations. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors on women’s career advancement in the Nepalese organization. The study showed that glass ceiling has a negative impact on women’s career advancement. It means that increase in glass ceiling leads to decrease in women’s career advancement. Similarly, mentoring has a positive impact on women’s career advancement. It indicates that increase in mentoring leads to increase in women’s career advancement. Moreover, the result also revealed that networking has a positive impact on women’s career advancement. It means that increase in networking leads to increase in women’s career advancement. Likewise, organizational structure has a positive impact on women’s career advancement. It shows that increase in organizational structure leads to increase in women’s career advancement. Similarly, family barrier has a negative impact on women’s career advancement. It shows that higher the family barrier, lower would be the women’s career advancement.